2021
DOI: 10.1371/journal.pone.0231068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a blend of essential oils in milk replacer on performance, rumen fermentation, blood parameters, and health scores of dairy heifers

Abstract: The aim of this study was to evaluate how the inclusion of a blend of essential oils in milk replacer (MR) affects different outcomes of dairy heifers. The outcomes evaluated: feed intake, performance, body development, blood cells and metabolites, insulin-like growth factor-1 (IGF-1), rumen fermentation, fecal scores, and respiratory scores. All outcomes were evaluated during pre-weaning (4–60 d of age), and carry-over effects during post-weaning (61–90 d of age) periods. The experimental units utilized were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
5
14
0
Order By: Relevance
“…Based on average temperature and DMI during the experiment, observed water intake for control group, EO, and VM were consistent with expected based on NRC [ 19 ], averaging 0.98, 1.01, and 0.97, respectively. The absence of effect of EO and VM on water intake has been reported previously [ 34 , 35 ]. In contrast, compared with the other treatments, supplementation with EO + ENZ increased (7%) water consumption.…”
Section: Discussionsupporting
confidence: 62%
“…Based on average temperature and DMI during the experiment, observed water intake for control group, EO, and VM were consistent with expected based on NRC [ 19 ], averaging 0.98, 1.01, and 0.97, respectively. The absence of effect of EO and VM on water intake has been reported previously [ 34 , 35 ]. In contrast, compared with the other treatments, supplementation with EO + ENZ increased (7%) water consumption.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, to increase effectiveness, especially in the rst 4 weeks of life, the feed additives should be provided in the liquid feed [21]. Also, a meta-analysis conducted by Frizzo et al [38] revealed that bene cial effects on calves' growth rate were observed when natural feed additives were added to milk replacer rather than to whole milk in the rst few weeks of life, which was resulted in fewer health and nutritional problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results showed that a eubiotic feed additive, consisting of a combination of a multi-strain probiotic (containing Lactobacillus casei, Lactobacillus salivarius, and Lactobacillus sakei) and herbal extracts with rosmarinic acid, as the main bioactive component, improved the health status (decreasing diarrhea occurrence, Cryptosporidium spp., and Giardia duodenalis prevalence), starter intake, total dry matter intake (TDMI), growth performance, and metabolic status of dairy calves during the preweaning period [20]. Feed additives can be mixed with liquid feeds, such as whole milk or milk replacer, or with solid feeds, such as the calf starter; however only very limited scienti c data are available comparing the effects of administering the feed additives with all these dietary offering methods on calf health, growth performance, and metabolic status during the preweaning period [21]. This information would be particularly useful for preventing infectious diseases that cause diarrhea and modeling the effect on growth of dairy calves, especially during the important preweaning period.…”
Section: Introductionmentioning
confidence: 99%
“…They were thawed and centrifuged at 13,000 rpm, for 15 min, at 13 °C. The supernatant was collected, filtered, and analyzed as previously described 22 .…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed to evaluate the effect of a commercial blend of EO supplementation in milk replacer (MR) on immunity, nutrient digestibility, organ development, and gene expression in dairy bull calves during the pre-weaning phase. Performance and carry-over effects were evaluated in our previous work 22 and were demonstrated in the present work with a descriptive purpose. We hypothesized that EO supplementation through liquid diet could enhance immune response, help gut development, and consequently, increase nutrient digestibility.…”
Section: Introductionmentioning
confidence: 99%